2013
DOI: 10.1007/s10552-013-0306-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose aspirin and survival in men with prostate cancer: a study using the UK Clinical Practice Research Datalink

Abstract: We found no evidence of an association between low-dose aspirin use before or after diagnosis and risk of prostate cancer-specific mortality, after potential confounders were accounted for, in UK prostate cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
1
27
2
Order By: Relevance
“…The latter findings are consistent with those of 3 observational studies that reported null associations with pre-diagnostic use of aspirin on prostate cancer mortality. 6,7,9 Taken together, these results argue against a protective association between the use of aspirin and the risk of prostate cancer mortality and all cause mortality. In light of a recent study reporting decreased prostate cancer mortality among high risk patients (HR 0.60 95% CI 0.37e0.99), 9 we performed a similar analysis but were not able to replicate these findings (HR 1.85 95% CI 1.51e2.30).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The latter findings are consistent with those of 3 observational studies that reported null associations with pre-diagnostic use of aspirin on prostate cancer mortality. 6,7,9 Taken together, these results argue against a protective association between the use of aspirin and the risk of prostate cancer mortality and all cause mortality. In light of a recent study reporting decreased prostate cancer mortality among high risk patients (HR 0.60 95% CI 0.37e0.99), 9 we performed a similar analysis but were not able to replicate these findings (HR 1.85 95% CI 1.51e2.30).…”
Section: Discussionmentioning
confidence: 94%
“…3 In contrast, the 2 other postdiagnostic studies reported null associations with point estimates close to the null value. 2,7 Several of the aforementioned observational studies had methodological shortcomings which may explain their discrepant results. Specifically, immortal time bias was present in 3 studies, 2,3,10 a bias that is the result of misclassifying unexposed person-time as exposed person-time in cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that met the inclusion criteria were all observational studies, comprising 20 case–control [9-11,16,17,21-23,26,28-33,35-37,41],[44] and 19 cohort studies [7,8,12-15,18-20,24,25,27,34],[39,40,42,43,45,46] involving more than 924,502 male subjects, including 108,136 PCa cases. Thirty-one studies (18 case–control [9-11,16,17,21-23,26,28-33,35-37] and 13 cohort [7,8,12-15,18-20,24,25,27,34]) addressed the use of any NSAID and its association with PCa incidence risk (Table 1); eight studies (two case–control [41,44] and six cohort [39,40,42,43,45,46]) investigated whether NSAID use was associated with PCa-specific mortality (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This group also found that aspirin use among patients with non-metastatic adenocarcinoma at diagnosis was associated with a reduced risk of subsequent metastasis (summary RR=0.45; 95% CI: 0.28–0.72) and cancer death (summary RR=0.50; 95% CI: 0.34–0.74) among 5 randomized trials of daily aspirin for the prevention of vascular events (130). Additional observational studies support an association between regular aspirin use after diagnosis and improved survival outcomes among breast (131, 132), colorectal [(133137), reviewed in (138)], and prostate cancer (139, 140) patients, while other studies do not (141144). Overall, the current evidence from long-term observational and randomized studies is strongly suggestive of a potential role for aspirin in the primary and secondary prevention of cancer.…”
Section: Ampk Role In Cancer: Human Studiesmentioning
confidence: 97%